Construction of Typical Vehicle Use Environment based on Virtual Simulation Test. (June 2020) - Kang, Hao; Chen, Youyi; Zhao, Hailong
Abstract: This paper puts forward the importance and advantage of using virtual simulation experiment to test the performance of vehicle environment. Through the construction of virtual pavement under different environments such as typical virtual test ground and wading test ground, the mobile performance experiment and capacity experiment of different types of heavy trucks were carried out, and the vehicle performance was evaluated as a whole. The virtual simulation test, by simulating the typical environment that may be encountered in the process of vehicle driving, collects the vehicle running state and driving parameters, studies and analyzes their performance, and provides an important basis for the improvement and improvement of vehicle design.